2021
DOI: 10.3390/life11060592
|View full text |Cite|
|
Sign up to set email alerts
|

Pro-Oxidative Effect of KIO3 and Protective Effect of Melatonin in the Thyroid—Comparison to Other Tissues

Abstract: Not only iodine deficiency, but also its excess may contribute to thyroid cancer. Potassium iodate (KIO3), which is broadly used in the salt iodization program, can increase oxidative damage to membrane lipids (lipid peroxidation, LPO) under experimental conditions, with the strongest damaging effect at KIO3 concentration of ~10 mM (corresponding to physiological iodine concentration in the thyroid). Melatonin is an effective antioxidant, which protects against KIO3-induced LPO in the thyroid. This study aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
21
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 58 publications
4
21
0
2
Order By: Relevance
“…Our study is probably the first attempt to compare the damaging effects of high iron concentrations in the thyroid and in various nonendocrine tissues under in vitro conditions. It should be stressed that the lower sensitivity of thyroidal membrane lipids, compared to that of membrane lipids in non-endocrine tissues, in response to high iron concentrations, is similar to previously observed pro-oxidative effects of KIO 3 (Iwan et al, 2021a). Therefore, we suppose that membrane lipids (and possibly other biological macromolecules) in the thyroid reveal higher resistance to any external pro-oxidative agent than those in other tissues.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Our study is probably the first attempt to compare the damaging effects of high iron concentrations in the thyroid and in various nonendocrine tissues under in vitro conditions. It should be stressed that the lower sensitivity of thyroidal membrane lipids, compared to that of membrane lipids in non-endocrine tissues, in response to high iron concentrations, is similar to previously observed pro-oxidative effects of KIO 3 (Iwan et al, 2021a). Therefore, we suppose that membrane lipids (and possibly other biological macromolecules) in the thyroid reveal higher resistance to any external pro-oxidative agent than those in other tissues.…”
Section: Discussionsupporting
confidence: 85%
“…One of the most famous antioxidants is melatonin (N-acetyl-5-methoxytryptamine), which is produced in the organism mostly by the pineal gland, but it is also available as an exogenous substance. This molecule is confirmed to be a very effective antioxidant and free radical scavenger which prevents oxidative damage not only in the thyroid (Lewinski and Karbownik, 2002;Karbownik et al, 2005;Kokoszko-Bilska et al, 2014;Zasada and Karbownik-Lewinska, 2015;Iwan et al, 2021aIwan et al, , 2021bStepniak et al, 2021) but also in many other tissues and organs (Karbownik et al, 2000(Karbownik et al, , 2001a(Karbownik et al, , 2001b(Karbownik et al, , 2006Gitto et al, 2001;Osuna et al, 2002;Mogulkoc et al, 2006;Reiter et al, 2017). In the current study, we have observed that melatonin reduced LPO induced by Fenton reaction substrates in all examined tissues, and this protective effect was independent of iron concentration.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…In the original article [ 1 ], there was a mistake in Figure 2 as published, namely the graph showing the levels of lipid peroxidation in the ovary was inserted twice and, at the same time, the graph showing the levels of lipid peroxidation in the spleen was not inserted at all. The corrected Figure 2 appears below.…”
mentioning
confidence: 99%